The Role of Activities in Teaching Arabic as a Second Language - Ahmed, Mohamed Mohi El-Din; Gad, Fardous Ahmed Mohamed; Amin, Elsayed Mohamed Abdalla (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
The activities play a significant role in teaching the Arabic language. They increase enthusiasm for learning, reduce boredom, and help develop language skills. This study aims to explore the role of activities in teaching Arabic to non-native speakers. The research adopted a descriptive methodology by distributing questionnaires to Arabic language teachers in Brunei's Arabic schools who participated in training courses held at the Teachers’ Training Institute for Religious Education in Bandar Seri Begawan (KUPUSB). One of the researchers participated in these courses as a trainer. The study found that the general use of activities in teaching Arabic is limited or rare, with an average of 2.0. Training students in activities was found to be very rare, with an overall average of 1.55. Teachers seldom train their students in activities such as Arabic cooking at school, debates, school radio programs, songs and chants, group speaking, plays and performances, or public speaking. The general attention to educational activities is minimal, with an average of 1.82. This explains the overall weakness in Arabic language skills, particularly speaking skills. This research highlights the importance of integrating activities into teaching Arabic, emphasizing the need to adopt active learning methods in teaching Arabic as a second language. It also encourages students to interact with the Arabic language through research, listening, reading, writing, and speaking, whether inside or outside the classroom.